Organizing national responses for rare blood disorders: the Italian experience with sickle cell disease in childhood. - Colombatti, Raffaella; Perrotta, Silverio; Samperi, Piera; Casale, Maddalena; Masera, Nicoletta; Palazzi, Giovanni; Sainati, Laura; Russo, Giovanna (Orphanet J Rare Dis, 2013)
BACKGROUND: Sickle cell disease (SCD) is the most frequent hemoglobinopathy worldwide but remains a rare blood disorder in most western countries. Recommendations for standard of care have been produced in the United States, the United Kingdom and France, where this disease is relatively frequent because of earlier immigration from Africa. These recommendations have changed the clinical course of SCD but can be difficult to apply in other contexts. The Italian Association of Pediatric Hematology Oncology (AIEOP) decided to develop a common national response to the rising number of SCD patients in Italy with the following objectives: 1) to create a national working group focused on pediatric SCD, and 2) to develop tailored guidelines for the management of SCD that could be accessed and practiced by those involved in the care of children with SCD in Italy. METHODS: Guidelines, adapted to the Italian social context and health system, were developed by 22 pediatric hematologists representing 54 AIEOP centers across Italy. The group met five times for a total of 128 hours in 22 months; documents and opinions were circulated via web. RESULTS: Recommendations regarding the prevention and treatment of the most relevant complications of SCD in childhood adapted to the Italian context and health system were produced. CONCLUSIONS: Creating a network of physicians involved in the day-to-day care of children with SCD is feasible in a country where it remains rare. Providing hematologists, primary and secondary care physicians, and caregivers across the country with web-based guidelines for the management of SCD tailored to the Italian context is the first step in building a sustainable response to a rare but emerging childhood blood disorder and in implementing the World Health Organization's suggestion "to design (and) implement … comprehensive national integrated programs for the prevention and management of SCD".
Keywords: Adolescent; Anemia, Sickle Cell; Child; Child, Preschool; Disease Management; Female; Hematologic Diseases; Humans; Infant; Infant, Newborn; Italy; Male; Neonatal Screening; Rare Diseases